studi komparatif stuktur tanah pada sistem pertanian berkelanjutan dan tradisional - Lahagu, Meiman Sanjay; Laoli, Tri boi Selamat (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This study aims to compare soil structure in sustainable and traditional agricultural systems, with a focus on soil physical and chemical parameters that influence soil fertility and the continuity of agricultural production. Sustainable farming systems employ practices such as crop rotation, composting, and the use of organic fertilizers, whereas traditional systems often rely on high chemical inputs. Data was collected through laboratory analysis of soil samples from both types of farming systems, including texture, organic matter content, pH and air holding capacity. The research results show that the soil in a sustainable farming system has a more stable structure, with a higher organic matter content and better ability to hold air compared to a traditional system. Meanwhile, traditional systems tend to cause degradation of soil structure and decrease in organic matter levels due to excessive use of chemical fertilizers and pesticides. These findings emphasize the implementation of sustainable practices to maintain agricultural quality and sustainability in the long term.